Adherence and chemoprevention in major cardiovascular disease: a simulation study of the benefits of additional use of statins. Issue 2 (7th January 2010) - Shroufi, A; Powles, J W
Abstract : Background: In everyday practice, adherence to preventive medication for cardiovascular disease (CVD) is lower than in clinical trials and appears to decline to ∼50% by about 5 years. The UK body for the evaluation of health technologies, NICE, currently recommends that persons with a >20% 10-year risk of incident cardiovascular disease receive statins. Methods: Publications on adherence to statin medication in clinical trials and in normal practice were systematically reviewed. Data on CVD-free members of a large southern hemisphere cohort study were used to simulate the expected benefits of contrasting strategies to increase the use of statins. Risks of incident CVD and death from CVD were estimated. Results: A strategy to enhance statin adherence among cohort members meeting NICE statin-prescribing guidelines resulted in about twice as large a reduction in the aggregate risk of CVD death as did a strategy to lower treatment thresholds. Conclusions: The benefits from increased spending on statin medication will be much greater if they result from enhanced adherence rather than from lowering the medication threshold.